INTERPENETRATING POLYMER NETWORK FILMS AS PIEZODIALYSIS MEMBRANES - GALIP, H (Huthig & Wepf Verlag, 1992)
In the present study, interpenetrating polymer network (IPN) membranes were investigated for their potential application as piezodialysis membranes. These IPN membranes are not mosaic membranes. It was found that some of these membranes did show piezodialysis effects. Two of the membranes tested under high pressure gave permeates which were found to be more concentrated in sodium chloride than the initial feed solution, when analyzed by differential refractometry. The permeates from one membrane were double checked by titrating the chloride ion with silver nitrate solution. The results of the titration also indicated a positive effect.
Keywords: Charge-Mosaic Membranes; Transport Properties